The neurobiological basis of sex differences in learned fear and its inhibition - Day, Harriet L. L.; Stevenson, Carl W. (The European journal of neuroscience, 2020)
Learning that certain cues or environments predict threat enhances survival by promoting appropriate fear and the resulting defensive responses. Adapting to changing stimulus contingencies by learning that such cues no longer predict threat, or distinguishing between these threat‐related and other innocuous stimuli, also enhances survival by limiting fear responding in an appropriate manner to conserve resources. Importantly, a failure to inhibit fear in response to harmless stimuli is a feature of certain anxiety and trauma‐related disorders, which are also associated with dysfunction of the neural circuitry underlying learned fear and its inhibition. Interestingly, these disorders are up to twice as common in women, compared to men. Despite this striking sex difference in disease prevalence, the neurobiological factors involved remain poorly understood. This is due in part to the majority of relevant preclinical studies having neglected to include female subjects alongside males, which has greatly hindered progress in this field. However, more recent studies have begun to redress this imbalance and emerging evidence indicates that there are significant sex differences in the inhibition of learned fear and associated neural circuit function. This paper provides a narrative review on sex differences in learned fear and its inhibition through extinction and discrimination, along with the key gonadal hormone and brain mechanisms involved. Understanding the endocrine and neural basis of sex differences in learned fear inhibition may lead to novel insights on the neurobiological mechanisms underlying the enhanced vulnerability to develop anxiety‐related disorders that are observed in women. We review studies on sex differences in learned fear inhibition. Overall, females show less fear extinction and discrimination than males, involving sex differences in the underlying brain areas. Estrogen regulates fear extinction and discrimination in females. Understanding the neurobiological basis of sex differences in learned fear inhibition may shed light on why women are more prone to anxiety, which is linked to deficits in learned fear inhibition and relevant neural circuit function.